2021
DOI: 10.3390/ijerph182111389
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward School Violence against LGBTQIA+. A Qualitative Study

Abstract: School climate is one of the main concerns in terms of research and intervention worldwide. Although it can be directed toward any student, some groups seem to be more vulnerable, as is the case of the LGBTQIA+ (lesbian, gay, bisexual, transgender, queer and intersex +) students, among others. Attitudes toward violence are a construct of particular importance for action plans focused on improving school coexistence. The aim of this study is to examine attitudes toward school violence against LGBTQIA+ students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…For example, Pina et al (2021a) concluded, in a study similar to this one, that attitudes toward school violence in the general population are related to violence to feel better about oneself, as a form of fun, perceived as legitimate, when directed at those who are different, when it has no consequences, as a way to resolve conflicts, as a way to socialize, and as a way to attract the attention of peers. Likewise, the study by Pina et al (2021b) identifies four types of attitudes toward violence directed toward students belonging to the LGBTQI + community were identified, these being the use of violence as a form of fun, to feel better, when it is perceived as legitimate and as a way of relating to members of this community. The results presented in both studies partially agree with ours, sharing two of the topics obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pina et al (2021a) concluded, in a study similar to this one, that attitudes toward school violence in the general population are related to violence to feel better about oneself, as a form of fun, perceived as legitimate, when directed at those who are different, when it has no consequences, as a way to resolve conflicts, as a way to socialize, and as a way to attract the attention of peers. Likewise, the study by Pina et al (2021b) identifies four types of attitudes toward violence directed toward students belonging to the LGBTQI + community were identified, these being the use of violence as a form of fun, to feel better, when it is perceived as legitimate and as a way of relating to members of this community. The results presented in both studies partially agree with ours, sharing two of the topics obtained.…”
Section: Discussionmentioning
confidence: 99%
“…For the exploration of aporophobia, focus group discussions were used following the methodology proposed by Krueger (1991). These focus groups involve a data collection technique, of a qualitative nature employed on numerous occasions in research (e.g., Edwards et al, 2020;Miranda Miranda et al, 2020;Pina et al, 2021b). For their formation, people with common characteristics that are relevant to the research topic are grouped together, in our case, minors from the same school and course.…”
Section: Data Collectionmentioning
confidence: 99%